Functional genomics for curation of variants in telomere biology disorder associated genes: a systematic review - Nelson, Niles; Feurstein, Simone; Niaz, Aram; Truong, Jia; Holien, Jessica K.; Lucas, Sionne; Fairfax, Kirsten; Dickinson, Joanne; Bryan, Tracy M. (Genetics in medicine, 2023)
Patients with an underlying telomere biology disorder (TBD) have variable clinical presentations, and they can be challenging to diagnose clinically. A genomic diagnosis for patients presenting with TBD is vital for optimal treatment. Unfortunately, many variants identified during diagnostic testing are variants of uncertain significance. This complicates management decisions, delays treatment, and risks nonuptake of potentially curative therapies. Improved application of functional genomic evidence may reduce variants of uncertain significance classifications.
Online veröffentlicht am 7. Dezember 2022, Artikelversion vom 20. Januar 2023
Gesehen am 22.11.2023